2003
DOI: 10.1002/maco.200390111
|View full text |Cite
|
Sign up to set email alerts
|

The use of electrochemical techniques for the investigation and monitoring of microbiologically influenced corrosion and its inhibition – a review

Abstract: The background of several electrochemical techniques -recording of the corrosion potential E corr , electrochemical impedance spectroscopy (EIS), electrochemical noise analysis (ENA) and recording of potentiodynamic polarization curves -has been discussed and examples of the use of these techniques in studies of microbiologically influenced corrosion (MIC) and MIC inhibition have been presented. These examples range from the use of the polarization resistance R p and the noise resistance R n in corrosion monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Figure 4 a shows the Nyquist plots of titanium immersed in enriched artificial saliva with S. sanguis , it is clearly found that all of the diagrams are a part of the imperfect semicircles and this can be attributed to the frequency dispersion [ 28 , 29 ]. The fact that diagrams have a depressed semicircular appearance shows that the corrosion of titanium is mainly controlled by a charge transfer process.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 a shows the Nyquist plots of titanium immersed in enriched artificial saliva with S. sanguis , it is clearly found that all of the diagrams are a part of the imperfect semicircles and this can be attributed to the frequency dispersion [ 28 , 29 ]. The fact that diagrams have a depressed semicircular appearance shows that the corrosion of titanium is mainly controlled by a charge transfer process.…”
Section: Resultsmentioning
confidence: 99%
“…EIS was employed to evaluate the corrosion behavior of the PVK–CPN coated films (PVK and PVK/MWNT) on SS coupons. EIS is considered to be a powerful tool in probing charge transfer phenomena and interfacial ion transfer on films 31, 32. The corrosion resistance of the bare SS, PVK coated SS, and PVK/MWNT‐modified SS were analyzed after immersion of the films in 0.5 M NaCl for 7 d. All samples show capacitive behavior as presented in the semi‐circle plot (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…These activities exert considerable control on the chemistry of fluids immediately adjacent to the metal surface [ 10 , 14 , 16 , 17 ]. Microbial activities can also limit the contact between O 2 or other corrosive compounds and the metal surface, inhibiting corrosion processes [ 18 24 ]; however, heterogeneous biofilms may induce corrosion through formation of differential aeration and concentration cells on the surface of the metal [ 25 29 ]. Given the diversity of mechanisms by which microbial activities may enhance and/or inhibit corrosion, it is necessary to develop a clear mechanistic understanding of the factors involved in MIC.…”
Section: Introductionmentioning
confidence: 99%